AUTHENTIC LEADERSHIP IN EDUCATION: A BALINESE PHILOSOPHICAL PERSPECTIVE THROUGH TRI KAYA PARISUDHA - I Wayan Aryawan; Ni Nyoman Sri Mastini (International Conference on Multidisciplinary Research Perspective, 2025)
Authentic leadership is increasingly discussed in the world of education because it emphasizes authenticity, reflective awareness, relational transparency, and moral consistency in decision-making. Previous research has shown that authentic leadership is able to increase trust, motivation, and performance in educational organizations. However, most research still focuses on Western perspectives and has not explored the integration of local wisdom as an ethical and spiritual foundation in educational leadership. This is where there is a research gap, namely how authentic leadership can be enriched with local philosophies that have strong moral and spiritual dimensions. This article aims to examine authentic leadership through the perspective of Balinese Hindu philosophy Tri Kaya Parisudha, which emphasizes purity of mind (manacika), speech (wacika), and deeds (kayika). The method used is a literature review with a conceptual-philosophical approach, which examines the theory of authentic leadership in education and connects it with the teachings of Tri Kaya Parisudha as the basis of local values. The analysis was carried out by mapping the linkages between the four dimensions of authentic leadership (self-awareness, relational transparency, internalized moral perspective, and balanced processing) with the three main pillars of Tri Kaya Parisudha. The results show that the integration of the two gives birth to a more complete authentic leadership model: educational leaders are not only consistent in their values and actions, but also uphold purity of thought, word, and deed. This model strengthens trust, harmony, and an ethical climate in the educational community while fostering a holistic character in students. These findings confirm that Balinese local wisdom has the universal potential to enrich the global discourse of educational leadership and provide an ethical framework that can be adapted to multicultural contexts.